Pengaruh Kombinasi Transcutaneous Electrical Nerve Stimulation (TENS), Quadriceps Setting Exercise, Dan Kinesio Taping Terhadap Aktivitas Fungsional Pada Osteoarthritis Genu Di RS Terpadu Di Bogor - Muhamad Rafly Ar Rasyid; Yohanes Deo Fau; Achmad Fariz; Agung Hadi Endaryanto (Jurnal Keperawatan Muhammadiyah, 2026)
Background: Knee osteoarthritis is a musculoskeletal disorder that commonly occurs in the productive age group and is associated with decreased functional ability and movement function. The combination of transcutaneous nerve stimulation, quadriceps setting exercise, and kinesio taping has been shown to improve functional outcomes. Objective: To determine the effect of a combination of transcutaneous nerve stimulation, quadriceps setting exercise, and kinesio taping on functional activity in patients with knee osteoarthritis at RS Terpadu Bogor. Methods: : This study employed a pre-experimental design with a pre-test and post-test approach. The study was conducted at RS Terpadu Bogor using a purposive sampling technique, with a total of 30 respondents. Functional outcomes were measured using the WOMAC questionnaire. Results: Hypothesis testing using the Wilcoxon test showed a significant result (p = 0.000), indicating that the combination of transcutaneous nerve stimulation, quadriceps setting exercise, and kinesio taping had a significant effect on functional activity in patients with knee osteoarthritis at RS TerpaduBogor. Conclusion: There is a significant effect of the combined intervention of transcutaneous nerve stimulation, quadriceps setting exercise, and kinesio taping on functional activity in patients with knee osteoarthritis at RS Terpadu Bogor.